E. Rekosh, K.A.Buchko, V. Terzieva (ed.): Pursuing The Public Interest - A Handbook for Legal Professionals and Activists.: Public Interst Law Initiative, Columbia Law School, New York 2001 - Zhřívalová, Petra (Lidé města, 2005)
A review of the book by E. Rekosh, K. A. Buchko and V. Terzieva.